Draft Genome Sequences of Type VI Secretion System-Encoding Vibrio fischeri Strains FQ-A001 and ES401 - Bultman, Katherine M. (Microbiol Resour Announc, 2019)
The type VI secretion system (T6SS) facilitates lethal competition between bacteria through direct contact. Comparative genomics has facilitated the study of these systems in Vibrio fischeri, which colonizes the squid host Euprymna scolopes. Here, we report the draft genome sequences of two lethal V. fischeri strains that encode the T6SS, FQ-A001 and ES401.